Data-Driven Games User Research - Zimmermann, Tom; Phillips, Bruce; Nagappan, Nachi; Harrison, Chuck (Proceedings of the CHI Workshop on Game User Research (CHI-GUR 2012), 2012)
In this paper we provide a brief introduction to some of the games user research activities at Microsoft. We focus on the analysis of automatically collected game data. We will show how this data can lead to insights about game usage and player progression.